Improved tests for Granger noncausality in panel data. (March 2023) - Xiao, Jiaqi; Karavias, Yiannis; Juodis, Artūras; Sarafidis, Vasilis; Ditzen, Jan
In this article, we introduce thextgrangert command, which implements the panel Granger noncausality testing approach developed by Juodis, Karavias, and Sarafidis (2021, Empirical Economics 60: 93–112). This test offers superior size and power performance to existing tests, which stem from the use of a pooled estimator that has a fasterN T convergence rate. The test has several other useful properties: it can be used in multivariate systems; it has power against both homogeneous and heterogeneous alternatives; and it allows for cross-section dependence and cross-section heteroskedasticity.